2022
DOI: 10.1002/sae2.12019
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable agricultural practices contribute significantly to One Health

Abstract: The One Health concept proposes that the health of humans, animals, and the environment are interconnected. Agricultural production is a critical component of One Health as food links the environment to human health. Food not only provides nutrients to humans but also represents an important pathway for human exposure to environmental microbes as well as potentially harmful agrochemicals. In addition, inappropriate agronomic practices can cause damage to the environment which can have unintended adverse impact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 110 publications
0
19
0
1
Order By: Relevance
“…in many crops 113 . Further, extensive use of chemical controls is increasingly discouraged due to both policy (for example, EU Green deals require 50% reduction in chemical pesticide use by 2030) and consumer demands, given their negative impacts on biodiversity including beneficial microorganisms, soil health and food quality (chemical residues), and ultimately human health 114 , 115 . Development of ecologically friendly chemicals needs prioritization, but these are currently expensive, and their development is time consuming.…”
Section: Paths Forwardmentioning
confidence: 99%
See 1 more Smart Citation
“…in many crops 113 . Further, extensive use of chemical controls is increasingly discouraged due to both policy (for example, EU Green deals require 50% reduction in chemical pesticide use by 2030) and consumer demands, given their negative impacts on biodiversity including beneficial microorganisms, soil health and food quality (chemical residues), and ultimately human health 114 , 115 . Development of ecologically friendly chemicals needs prioritization, but these are currently expensive, and their development is time consuming.…”
Section: Paths Forwardmentioning
confidence: 99%
“…and Fusarium spp. ), vectors of human pathogens ( Escherichia coli , Salmonella spp., Listeria monocytogenes in lettuce and other vegetables and fruits), antimicrobial resistance (transfer of antimicrobial resistance from food microbiomes to human gut microorganisms) and exposure to harmful chemical pesticides (for example, organophosphate chronic exposure and their carcinogenic and genotoxic effects) 114 , 136 . Explicit consideration of plant diseases in the One Health concept can provide an effective framework to simultaneously mitigate risks of human health that are directly linked to plant health (for example, human infection, agrochemicals) and spread of plant diseases.…”
Section: Paths Forwardmentioning
confidence: 99%
“…All these results indicate that the crop host has a strong selection effect on the keystone taxa of the crop microbiome across plant developmental stages and under different environmental stresses. Additionally, whilst our understanding of keystone taxa of soil and crop microbiomes is advancing, increasing studies have indicated that some potential soil‐borne human pathogens such as Clostridium botulinum , Salmonella enterica , and Burkholderia pseudomallei may transfer to human system via soil–plant–food chains (Brevik et al, 2020; Nieder et al, 2018; Samaddar et al, 2021; Yan et al, 2022). However, our knowledge of ecological mechanisms that influence this harmful microbial loop along the soil–plant–food continuum is still limited.…”
Section: Microbial Interactions and Keystone Taxa Of Crop‐associated ...mentioning
confidence: 99%
“…The recovery of animal waste is the main critical point [16,17]. Research in this context has been aligned with techniques to inactivate pathogens, eliminate veterinary antibiotics, reduce potentially harmful agrochemicals in food, and investigate the microbiome and resistome transmission pathways from manure to soil and crops [18,19]. However, the health effects are only partially understood, and much more comprehensive evidence to better inform the policy debate is lacking [20].…”
Section: Introductionmentioning
confidence: 99%
“…This concept promotes balanced well-being between humans, animals, and the environment, providing a global strategy that highlights the need for holistic and transdisciplinary approaches to improve the connection of all components of an ecosystem [21]. Horticulture presents an intrinsic closeness to this tripartite interaction, playing an essential role as food represents the link between soil, plants, and animals for human health [19]; therefore, circular horticulture, especially for the valorization of animal biomass, can be strongly influenced by the One Health concept. The need for circular practices based on One Health is expected to increase in the future [22].…”
Section: Introductionmentioning
confidence: 99%